Orzeł i lew jako dwie przeciwstawne sobie siły czasów ostatecznych w Czwartej Księdze Ezdrasza - Miduch, Maria Elżbieta (Verbum Vitae, 2017)
The Fourth Book of Ezra is one of the Jewish apocryphal apocalypses, written after the destruction Jerusalem Temple. It is a theological reflection on the difficult reality in which Jews participate. The author of 4 Ezra employs symbols in order to project a particular vision of his world, especially zoomorphic symbols. These were not only easy for his first century Jewish readers to relate to but also simple for them to identify and interpret as to their meaning. The Vision of the Eagle and the Lion is a key element of the apocalyptic concept of the book: It symbolizes the power of evil, which is nevertheless defeated by the messiah.